2012
DOI: 10.5430/jnep.v2n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Dutch nursing students’ knowledge and attitudes towards older people - A longitudinal cohort study

Abstract: Background: Due to changing demographics in the population, the majority of current nursing students will work mostly with older people after graduation. It is known that most nursing students have little knowledge and interests in working with older people. There is a growing need for motivated nurses to provide care for older people as the quality of care is influenced by their attitudes. The objective of this study is to investigate Dutch nursing students' knowledge of and attitudes toward older people and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 25 publications
7
48
2
3
Order By: Relevance
“…A number of academics have stated that course work about older people is essential to acquire knowledge, understanding, skills and to dispel myths (Bleijenberg et al, 2012;Flood and Clark, 2009;King et al, 2013;Runkawatt et al, 2013;Usta et al, 2012;Vefikulucay, 2008). King et al (2013) found a stand-alone gerontological nursing course produced positive attitudes toward older people as did Baumbusch et al acute medical and surgical where the focus was on praxis and not specifically care of older people (Holroyd et al, 2009).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…A number of academics have stated that course work about older people is essential to acquire knowledge, understanding, skills and to dispel myths (Bleijenberg et al, 2012;Flood and Clark, 2009;King et al, 2013;Runkawatt et al, 2013;Usta et al, 2012;Vefikulucay, 2008). King et al (2013) found a stand-alone gerontological nursing course produced positive attitudes toward older people as did Baumbusch et al acute medical and surgical where the focus was on praxis and not specifically care of older people (Holroyd et al, 2009).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The limited number of nurses wanting to work with older people after graduation has been supported by other studies. Haron et al [7] found 12% Israelis nursing students considered working with older people, while Bleijenberg et al [8] found only 2.7% Dutch nursing students expressed a preference for working with older people after graduation.…”
Section: Introductionmentioning
confidence: 98%
“…The two other questionnaires were the Aging Semantic Differential scale and a translated version of the Kogan scale[15] to measure attitudes towards older persons. The Aging Semantic Differential is a 7-point scale consisting of dichotomies at either end of the scale, containing 32 adjectives[16].…”
Section: Methodsmentioning
confidence: 99%